FATTY ACIDS CONTENT OF KAHAI (CARYODENDRON ORINOCENSE KARST) SEEDS CULTIVATED IN AMAZONIAN OF ECUADOR - W, Carrillo; J, Greffa; D, Vinueza; M, Ãlvarez; M, Silva; C, Carpio; D, Morales (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The aim of this study was to identify fatty acids present in a kahai oil sample cultivated in the Amazonian area of Ecuador. Methods: Kahai oil was obtained from kahai seeds using the cold pressing method. Fatty acids analysis was carried out using the gas chromatography with a mass selective detector and using the database Library NIST 14.L to identify the compounds. Results: Kahai seeds have 62.36% of total lipids. Kahai seeds have a high content of polyunsaturated fatty acids with 68.04% of linoleic acid and 2.90% of linolenic acid. Kahai oil has 18.59% of monounsaturated fatty acids of oleic acid. Kahai oil only has 7.0% of palmitic acid and 3.47% of stearic acid. Conclusions: Kahai oil is a good source of polyunsaturated fatty acids omega 6 and has a good proportion of monounsaturated fatty acid omega 9. This oil can be used in cosmetic and pharmaceutical and functional foods for their composition of fatty acids. Kahai oil can be an alternative of crop to indigenous communities in the Amazonian area of Ecuador.